Parasitic coinfections among selected smallholder goat flocks in Malaysia - B. T., Paul; A., F. F. Jesse; Kamaludeen, J.; Chung, E. L. T.; K., Mat Isa; Azhar, N.A.; Jimale, Y.A.; Mohd Lila, M.A. (Malaysian Society of Parasitology and Tropical Medicine, 2024)
This paper describes the occurrence of multiple parasitic infection with special reference to emerging haemotropic Mycoplasma ovis. A cross-sectional survey of four selected goat flocks was conducted to collect samples and management information. Blood samples were processed using microhaematocrit centrifugation to determine the packed cell volume (PCV). Detection and morphological identification of blood protozoa and haemotropic Mycoplasma ovis from Giemsa-stained smears were done microscopically. M. ovis infection was classified mild (1-29% infected cells), moderate (30-59% infected cells), or severe (above 60% infected cells). Faecal floatation and McMaster faecal egg count were used to detect and classify strongyle infections as negative (no eggs/oocysts), light (< 500 epg), Moderate (500 – 1000 epg), or severe (>1000 epg) and coccidia infection as light (<1800 opg), moderate (1800 – 6000 opg), or severe (>6000 opg). There were 149 goats with blood protozoa (57.98%; 95% CI: 51.87 – 63.85) and 204 goats with GI parasites (79.38%; 95% CI: 74.02 - 83.87) involved in single (15.8%; 95% CI: 11.7 – 21.0) or multiple (84.2%; 95% CI: 79.0 – 88.3) infections. The risk of Strongyles increases by 2.49 (95% CI: 1.24 – 4.99) in females versus males and 6.79 (95% CI: 3.25 – 14.18, p =0.000) in adults versus young. The risk of Eimeria species increases by 7.32 (95% CI: 3.45 – 15.50, p =0.000) in adults versus young, while M. ovis coinfection risk increases by 4.51 (95% CI: 1.40 – 14.50, p =0.000) in female versus males. Thin animals had a significantly higher (p<0.05) mean burden of Strongyle (1370.37 ± 345.49) and Eimeria (1594.12 ± 695.26) than the moderate and fat goats. The PCV was negatively associated with mean faecal egg count (FEC) (p<0.05) such that a lower PCV was recorded in animals with a higher Strongyle epg output. A severe burden of M. ovis was accompanied by an increased nematode FEC and decreased haematocrit (p<0.05). Coinfections of Strongyles, or Eimeria species involving M. ovis were associated with a higher parasitaemia compared with single infections (p<0.05). This study highlights the importance of M. ovis and Strongyle or Eimeria species coinfections among goat flocks and provides valuable data for developing and implementing an integrated herd health management program for parasite control among low-input smallholder flocks.